Pregnant Women's Knowledge and Attitudes About Pregnancy Care: The Effect of Using the Ebumil Android Application - Kartini; Farming; Sabur, Fitriati (Public Health of Indonesia, 2025)
Background: Maternal and infant health is still one of the issues that receive special attention related to improving the quality of human life in the world. Every hour, one woman dies during childbirth or due to causes related to pregnancy. There are still many pregnant women who are less aware of the importance of examination as an effort to detect pregnancy risk factors. Lack of knowledge and attitude, makes pregnant women less aware of the emergence of symptoms of certain dangerous diseases, either indirectly causing maternal death. Objective: The purpose of the study was to determine the knowledge and attitudes of pregnant women after being given education through the Ebumil android application. Methods: The study used a quasi-experimental approach. The sample was 120 pregnant women who were divided into two groups, namely the intervention group (which was given education through the ebumil application and the control group (which was not given education through the ebumil application) using a simple random sampling technique. The research variables were knowledge and attitudes of pregnant women. The research instrument data was a knowledge and attitude questionnaire. The analysis test used was the paired t test. Results: The results of the study showed an increase in knowledge in the intervention group of 80.03 (post 1) and 90.50 (post 2) while the control group did not experience an increase in knowledge of 40.98 (post 1) and 40.50 (post 2). There was an increase in attitudes in the intervention group of 78.16 (post 1) and 90.25 (post 2) while the control group did not experience an increase in attitudes of 42.84 (post 1) and 42.35 (post 2). The results of the paired t test statistical test obtained a p-value of 0.000 <α=0.05, this states that there is an effect of providing education through the application ebumil on the knowledge and attitudes of pregnant women about pregnancy care. Conclusion: The conclusion is that there is an effect of providing education through the ebumil application on the knowledge and attitudes of pregnant women about pregnancy care and there is an increase in the knowledge and attitudes of pregnant women after being given education through the ebumil android application. It is hoped that pregnant women can respond and take the best steps in maintaining their pregnancy with the online knowledge that has been obtained. Keywords: knowledge, attitude, application of ebumil